Analysis of the Drivers and Obstacles to Changes in Management Accounting at Regional General Hospital in West Surabaya - Yuli Ermawati; Pujianto (Journal of Economy, Accounting and Management Science (JEAMS), 2019)
The impact of technological developments and globalization is also felt in the hospital industry. The tight competition in the hospital industry requires hospital managers to be more careful in carrying out hospital management. Inaccurate management can cause low quality of service, inefficiency of the organization, low welfare of employees, and can even cause chaos in hospital organizations. Although the characteristics of a hospital organization are not the same as the characteristics of a business organization, business management principles can be adopted in hospital organizations. This is supported by the government through Law No.1 / 2004 concerning the State Treasury. This study analyzes the role of the design of existing management accounting systems. Furthermore, this study will examine whether triggers and obstacles can affect changes in management accounting. Because changes in management accounting policies can affect how the performance and service of the hospital. The research method used in this study is a quantitative method. To analyze data Structural Equation Modeling (SEM) analysis of the PLS statistical software package is used in the model and hypothesis testing. The results of this study are factors that strengthen or support attitudes towards changes in management accounting implemented by management are staffing factors, transparency, board expectations, agency problems, IT, and data quality. Factors that inhibit or do not support the attitude towards management accounting changes applied by management are the factors of cost, profitability, incentives, organizational change, behavioral control and environmental factors.